Shifts in the spatiotemporal profile of inflammatory phenotypes of innate immune cells in the rat brain following acute intoxication with the organophosphate diisopropylfluorophosphate - Peter M. Andrew; Jeremy A. MacMahon; Pedro N. Bernardino; Yi-Hua Tsai; Brad A. Hobson; Valerie A. Porter; Sydney L. Huddleston; Audrey S. Luo; Donald A. Bruun; Naomi H. Saito; Danielle J. Harvey; Amy Brooks-Kayal; et al. (Journal of Neuroinflammation)
Abstract Acute intoxication with cholinesterase inhibiting organophosphates (OP) can produce life-threatening cholinergic crisis and status epilepticus (SE). Survivors often develop long-term neurological consequences, including spontaneous recurrent seizures (SRS) and impaired cognition. Numerous studies implicate OP-induced neuroinflammation as a pathogenic mechanism contributing to these chronic sequelae; however, little is known about the inflammatory phenotype of innate immune cells in the brain following acute OP intoxication. Thus, the aim of this study was to characterize the natural history of microglial and astrocytic inflammatory phenotypes following acute intoxication with the OP, diisopropylfluorophosphate (DFP). Adult male and female Sprague–Dawley rats were administered a single dose of DFP (4 mg/kg, sc) followed by standard medical countermeasures. Within minutes, animals developed benzodiazepine-resistant SE as determined by monitoring seizures using a modified Racine scale. At 1, 3, 7, 14, and 28 d post-exposure (DPE), neuroinflammation was assessed using translocator protein (TSPO) positron emission tomography (PET) and magnetic resonance imaging (MRI). In both sexes, we observed consistently elevated radiotracer uptake across all examined brain regions and time points. A separate group of animals was euthanized at these same time points to collect tissues for immunohistochemical analyses. Colocalization of IBA-1, a marker for microglia, with iNOS or Arg1 was used to identify pro- and anti-inflammatory microglia, respectively; colocalization of GFAP, a marker for astrocytes, with C3 or S100A10, pro- and anti-inflammatory astrocytes, respectively. We observed shifts in the inflammatory profiles of microglia and astrocyte populations during the first month post-intoxication, largely in hyperintense inflammatory lesions in the piriform cortex and amygdala regions. In these areas, iNOS+ proinflammatory microglial cell density peaked at 3 and 7 DPE, while anti-inflammatory Arg1+ microglia cell density peaked at 14 DPE. Pro- and anti-inflammatory astrocytes emerged within 7 DPE, and roughly equal ratios of C3+ pro-inflammatory and S100A10+ anti-inflammatory astrocytes persisted at 28 DPE. In summary, microglia and astrocytes adopted mixed inflammatory phenotypes post-OP intoxication, which evolved over one month post exposure. These activated cell populations were most prominent in the piriform and amygdala areas and were more abundant in males compared to females. The temporal relationship between microglial and astrocytic responses suggests that initial microglial activity may influence delayed, persistent astrocytic responses. Further, our findings identify putative windows for inhibition of OP-induced neuroinflammatory responses in both sexes to evaluate the therapeutic benefit of anti-inflammation in this context.